Issuance Plan for Government Securities : Guidance Note - World Bank Group (World Bank, Washington, DC, 2016)
The issuance plan sets out the government’s intentions for the issuance of its debt securities in the domestic capital markets. It includes the bonds and bills to be issued and the timing of issuance, and may include general information on other operations that the government intends to undertake with its debt securities, such as buybacks and exchanges. This guidance note describes the key considerations for the debt manager and the steps involved in developing and implementing the issuance plan.